Integration of Islamic values within science based on Islamization of human knowledge (IOHK) theory or philosophy - Yaacob, Solehah@Nik Najah Fadilah; Haron, Ismail (Transnational Press London Ltd, 2024)
This discussion on the integration of Islamic values within the sciences is focused mainly on the views and preoccupation of Malaysian proponents of the Islamization of human knowledge (IOHK) concept who expressed their views and views of their other Muslim associates either in Malaysia or abroad. Necessarily, a historical backdrop on the significance and centrality of knowledge in Islamic civilization is mentioned to emphasize why some proponents of IOHK regard this approach as a jihad of the 21st century. It is in particular to them a jihad to restore science to its rightful position within the trajectory in conformity with the teaching of Islam so that science would not be used without impunity to fuel human greed that could cause serious hazards to humankind. Islamization enterprise or Islamicization (a more appropriate term ) has been triggered mainly to protect the sanctity of knowledge as conceived and understood in the Islamic perspective from the onslaught of the conception of knowledge purported by Western scientists and scholars within the worldview formed and shaped by naturalism, materialism, and positivism perspectives. The analytical and critical approaches are used as methods of discussion.